From Lukács to the Frankfurt School - Lima, Bruna Della Torre de Carvalho; Santos, Eduardo Altheman Camargo (Faculdade de Filosofia e Ciências, 2021)
Translation of the chapter  "From Lukács to the Frankfurt School"